Perceived land tenure security and rural transformation: Empirical evidence from Ghana - Ghebru, Hosaena; Khan, Huma; Lambrecht, Isabel B. (International Food Policy Research Institute, 2016)
Tenure security is believed to be critical in spurring agricultural investment and productivity. Yet what improves or impedes tenure security is still poorly understood. Using household- and plot-level data from Ghana, this study analyzes the main factors associated with farmers’ perceived tenure security. Individually, farmers perceive greater tenure security on plots acquired via purchase or inheritance than on land allocated by traditional authorities. Collectively, however, perceived tenure security lessens in communities with more active land markets and economic vibrancy. Migrant households and women in polygamous households feel less secure about their tenure, while farmers with political connections are more confident about their tenure security.